2018
DOI: 10.3389/fmicb.2018.02194
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bradyrhizobia in Subsahara Africa: A Rich Resource

Abstract: Making use of biological nitrogen fixation (BNF) with pulses and green manure legumes can help to alleviate nitrogen deficiencies and increase soil fertility, problems faced particularly in smallholder agriculture in Subsahara Africa (SSA). The isolation of indigenous rhizobia provides a basis for the formulation of rhizobial inoculants. Moreover, their identification and characterization contribute to the general understanding of species distribution and ecology. Here we discuss global species discovery of Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…1) based on common geographic origin suggests the presence of country-specific Bradyrhizobium strains responsible for Kersting’s groundnut nodulation in the wider geographic locations studied. The influence of geographic location on the distribution of rhizobia has been previously reported for cowpea isolates from Senegal and Ghana (15, 18, 28). In this study, the isolates from Nelspruit in South Africa were the most diverse, as shown by their presence in 13 out of the 23 major BOX-PCR clusters identified; this is in agreement with earlier studies which also revealed greater diversity among South African bradyrhizobial populations nodulating cowpea and Bambara groundnut than in isolates from Ghana or Botswana (12, 16).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…1) based on common geographic origin suggests the presence of country-specific Bradyrhizobium strains responsible for Kersting’s groundnut nodulation in the wider geographic locations studied. The influence of geographic location on the distribution of rhizobia has been previously reported for cowpea isolates from Senegal and Ghana (15, 18, 28). In this study, the isolates from Nelspruit in South Africa were the most diverse, as shown by their presence in 13 out of the 23 major BOX-PCR clusters identified; this is in agreement with earlier studies which also revealed greater diversity among South African bradyrhizobial populations nodulating cowpea and Bambara groundnut than in isolates from Ghana or Botswana (12, 16).…”
Section: Discussionmentioning
confidence: 66%
“…Several studies have reported the presence of high diversity among rhizobial populations responsible for grain legume nodulation in African soils (1218). Globally, the list of N 2 -fixing rhizobia responsible for legume nodulation consists of over 100 species from 14 bacterial genera originating from diverse legumes and contrasting environments across different continents (19).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as recently noted by Grönemeyer and Reinhold-Hurek [ 23 ], our knowledge on the diversity and biogeography of bradyrhizobia species relies primarily on data collected in the Americas, Asia and Europe. For examples, type strains of the B. elkanii supergroup include B. icense LMTR 13 T isolated from Phaseolus lunatus in Peru [ 24 ]; B. macuxiense UFLA03-321 T found inside a nodule of Centrolobium parense in Amazonia [ 25 ] and B. retamae Ro19 T identified as a symbiont of Retama monosperma in the Mediterranean basin [ 26 ].…”
mentioning
confidence: 99%
“…The key mineral nutrients N and P are in very low concentrations, for example, in sandy soils of Northern Namibia ( Gröngröft et al, 2013 ). In-depth knowledge on rhizobial symbionts in Subsahara Africa is still limited ( Grönemeyer and Reinhold-Hurek, 2018 ), although Africa is a center of origin of many legumes (e.g., cowpea and Bambara groundnut), and offers a rich diversity of wild legume species ( Sprent et al, 2010 ; Pule-Meulenberg, 2014 ; Lemaire et al, 2015a ). Thus, the diversity of Bradyrhizobium species in Subsahara Africa may be as yet underestimated and represents a hidden rich resource for inoculant development in future ( Grönemeyer and Reinhold-Hurek, 2018 ).…”
Section: Introductionmentioning
confidence: 99%